Indications for Caesarean Section and its Fetal and Maternal Outcome in a Teaching Hospital, Province Five, Nepal - Asha Panth; Sarswoti Kumari Gautam; Sunita Acharya (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Cesarean section (CS) is an operative technique by which a fetus is delivered through an abdominal and uterine incision and is effective in saving maternal and infant lives but caesarean section rates higher than 10% are not associated with reductions in maternal and newborn mortality rates. The objective of the study was to find out the indications for caesarean section and its fetal and maternal outcomes in a Teaching Hospital, Province Five, Nepal.